The reterritorialization and the struggle for water of those affected by the transposition of the São Francisco River in the Brazilian Northeast - Santos, Jaqueline Guimarães; Pedrozo, Eugenio Avila; Ioris, Antonio (Sociedade & Natureza, 2022)
The implementation of the largest Brazilian hydrological project, the Projeto de Integração do rio São Francisco – PISF (water resources project implemented by the federal government in the Brazilian Northeast), responsible for transfering the river’s waters into the semi-arid Northeast region of Brazil, had different effects in the region and caused the deterritorialization of several families. A portion of these families were reterritorialized into the 18 rural villages scattered throughout the project, where approximately 845 families were resettled. In this context, the research conducted in the rural village of Lafayette, in Monteiro/PB, aims to analyze the process of reterritorialization of the affected actors and their strategies to fight for access to water. For this purpose, we adopted a qualitative approach and ethnographic research, using procedures such as oral history interviews with actors resettled in the village, semi-structured interviews with institutional actors, in addition to collecting documents, photographs and observations recorded in the field diary. The results demonstrate the difficulties faced by families in the process of reterritorialization in the village, the emergence of conflicts over water, in addition to apprehending the different strategies of struggle of the affected actors to obtain access to water for human consumption. In this way, the study contributes to the problematization regarding those affected by the project and the access to water within such a large project whose motto is the distribution of water, though the lives of the affected families remain barren.